2017
DOI: 10.1038/s41598-017-11342-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin Promotes Cardiac Progenitor Cell Survival against Oxidative Stress via the Upregulation of the NFκB/iNOS Signal Pathway and Nitric Oxide Production

Abstract: Human cardiac stem/progenitor cells (hCPCs) may serve in regenerative medicine to repair the infarcted heart. However, this approach is severely limited by the poor survival of donor cells. Recent studies suggest that the mammalian globin cytoglobin (CYGB) regulates nitric oxide (NO) metabolism and cell death. In the present study, we found that CYGB is expressed in hCPCs. Through molecular approaches aimed at increasing or decreasing CYGB expression in hCPCs, we found that CYGB functions as a pro-survival fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 59 publications
(77 reference statements)
2
27
0
Order By: Relevance
“…Although recent studies have investigated antioxidant systems in hypertension and its role to oppose oxidative stress [ 31 , 32 ], very few is known about their response to exercise training in the heart of hypertensive individuals. Therefore, we also analyzed in the LV of both strains the effects of aerobic training on several antioxidant enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent studies have investigated antioxidant systems in hypertension and its role to oppose oxidative stress [ 31 , 32 ], very few is known about their response to exercise training in the heart of hypertensive individuals. Therefore, we also analyzed in the LV of both strains the effects of aerobic training on several antioxidant enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of iNOS, activation can result in positive feedforward accumulation of iNOS, resulting in a pathogenic effect. ( 33 ) We measured Nos1, Nos2 (iNOS), and Nos3 levels in the livers of mice from the eight groups and found that while Nos1 and Nos3 were unchanged or down‐regulated in knockout mice (Supporting Fig. ), iNOS expression was induced in the male PRMT1‐knockout mice fed alcohol, the group with the highest median tumor number (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Human cardiac progenitor cells (hCPCs) were isolated from the right atrial appendage and sorted for expression of c-kit cell surface marker, as described previously (Zhang et al, 2017). Cells were used at passage 7-10 for these studies.…”
Section: Culture Of Cardiac Progenitor Cellsmentioning
confidence: 99%